Role of NMDA and AMPA glutamatergic receptors in the effects of social defeat on the rewarding properties of MDMA in mice. (24th October 2018) - García‐Pardo, M. P.; Miñarro, J.; Llansola, M.; Felipo, V.; Aguilar, M. A.
Abstract: Exposure to social stress alters the response to drugs of abuse of experimental animals. Changes in the glutamatergic system seem to play a role in the effects of social defeat stress on the rewarding properties of cocaine and amphetamine. The aim of the present study was to evaluate the involvement of N ‐methyl‐D‐aspartate (NMDA) and α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid (AMPA) glutamate receptors in the effects of social defeat on the conditioned place preference induced by 3, 4‐methylenedioxymethamphetamine (MDMA). Our hypothesis was that changes in these receptors could mediate the effects of social defeat on MDMA reward. Young adult male mice were exposed to an episode of social defeat with an aggressive conspecific immediately before each conditioning session with MDMA (1.25 mg/kg, four sessions on alternating days). According to the treatment received before defeats, six groups were used: saline, 5 or 10 mg/kg of memantine (NMDA antagonist) and 0.25, 1 or 5 mg/kg of 6‐cyano‐7‐nitroquinoxaline‐2, 3‐dione (CNQX) (AMPA antagonist). One control group was exposed to exploration before place conditioning. In two additional defeated and control groups, the membrane expression of NMDA and AMPA receptors was determined in the striatum and the hippocampus. Control and memantine‐treated groups developed place preference, but not defeated mice treated with saline or CNQX, suggesting that the blockade of NMDA receptors reversed the effects of social defeat. Social defeat decreased the expression of several subunits of NMDA and AMPA receptors, mainly GluN1 and GluA1. These results demonstrated that glutamatergic plasticity is involved in the effects of social defeat stress on MDMA reward. Abstract : Acquisition of conditioned place preference induced by 3, 4‐methylenedioxymethamphetamine (MDMA) (1.25 mg/kg) in young adult male mice is impaired by exposure to social defeat before each conditioning session with the drug. Administration of the N ‐methyl‐D‐aspartate (NMDA) antagonist memantine reversed the impairing effects of social defeat on MDMA conditioned place preference. Exposure to social defeat decreased the expression of several subunits of NMDA and α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid receptors, mainly GluN1 and GluA, in the striatum and hippocampus, 48 h after the last episode of social defeat.